THE EVOLUTION OF AXIAL SPONDYLOARTHRITIS DURING 12-MONTH FOLLOW-UP STUDY OF A CORSAR COHORT - Sh. F. Erdes; T. V. Dubinina; O. A. Rumyantseva; A. B. Dyomina; E. E. Gubar; D. G. Rumyantseva (Научно-практическая ревматология)
Until recently there is no clarity in the nosological independence of non-radiographic axial spondyloarthritis  (nraxSpA). Cohort studies can assist in solving this problem. In 2013, the V.A. Nasonova Research Institute of Rheumatology started to form a Cost and Resource utilization Study in Antiretroviral treated patients (CoRSaR) cohort to investigate the evolution of nr-axSpA and treatment policy for this condition.  This communication deals with the preliminary results of a 12-month follow-up study of the CoRSaR  cohort.Subjects and methods. The cohort was recruited  from all consecutive patients with a < 5-year history of nr-axSpA who sought for medical advice and treatment. The patients were examined in accordance  with the Ankylosing Spondylitis Assessments (ASAS) International Working Group  guidelines at inclusion and after 12 months.A total of 94 patients with axSpA were enrolled; 54 patients out of them were included into a preliminary analysis of the evolution of axSpA; their mean age at inclusion was 27.1±5.5  years and the mean disease duration  was 22.4±15.1 months;  49 (90.7%) patients were HLA-B27 positive. 31 of the 54 patients had ankylosing spondylitis(AS) and 23 had nr-axSpA.Results and discussion. The patients with AS and those with nr-axSpA showed virtually no difference in main clinical parameters,  such as the presence of arthritis, enthesitis, BASDAI, ASDAS-CRP, and BASFI. By the end of the 12month follow-up, both groups virtually displayed almost a double reduction  in all inflammatory markers but erythrocyte sedimentation rate. Nine (39%) patients with nr-axSpA developed radiographic sacroiliitis over 12 months and the diagnosis of AS was confirmed.Conclusion. 39% patients with nr-axSpA developed radiographic sacroiliitis at the 12-month follow-up. Nr-axSpA should be regarded as an early stage of AS.